A Tale of Two Roads: Groundwater Depletion in the North China Plain - Ujjayant Chakravorty; Xiangzheng Deng; Yazhen Gong; Martino Pelli; Qian Zhang (Center for Economic Studies and ifo Institute (CESifo), 2023)
There is a large literature on the role infrastructure plays in economic development, but few papers document the causal effect of infrastructure on the sustainability of natural resources. We examine the effect of the arrival of two new national highways on ground water levels in a small agricultural county in the North China Plain - a region that produces most of the nation's food grains. We first develop a conceptual framework to show that farmers located closer to the highways devote more acreage to crops that are water intensive. We then use a unique GIS-referenced dataset of all the 12,160 tube wells in this county to show that highway construction accelerates the drilling of new wells in farms closer to the highway. In addition, there is greater depletion of the groundwater in wells near the two highways relative to wells located farther away. Our estimated depletion rates near the two roads are at least 5 times higher relative to mean depletion rates in the North China Plain. We show suggestive evidence that depletion is caused by a switch from subsistence to commercial cropping, and intensification of farming practices adjacent to the highway. These results suggest that the environmental cost of new infrastructure building may be significant and needs to be incorporated in benefit-cost analysis.
Keywords: O13; O18; Q25; 330; infrastructure; roads; North China Plain; water resources; sustainability